Asuhan Keperawatan Pada Tn. W Dengan Gangguan Sistim Pernafasan : Penyakit Paru Obstruksi Kronik (PPOK) Di Ruang Anggrek Bougenvile RSUD Pandan Arang Boyolali - Rahmadi, Yasir; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2015)
NURSING CARE ON MR.W WITH RESPIRATORY SYSTEM DISORDERS: CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) IN PANDAN ARANG GOVERNEMENT HOSPITAL OF BOYOLALI Abstract Background: Chronic Obstructive Pulmonary Disease (COPD) is a disease that affects many Indonesian people. Incidence of COPD in Indonesia is the fifth highest in the world with 7.8 million cases recorded. The most common cause of COPD that often found in general hospitals is because people's unhealthy lifestyle, such as smoking habit and the air pollution, which can trigger COPD.Objective: To determine the nursing care in patients with COPD include assessment, intervention, implementation, and evaluation of nursing care.Methods: The method used was to perform nursing care in patients with COPD that includes assessment, intervention, implementation and evaluation of nursing care.Results: In patients Mr.W with COPD, he experienced shortness of breath, difficult to move and insomnia, so the defined diagnosis were: ineffectiveness airway clearance was associated with excess of mucus production; activity intolerance was related to imbalance demand and supply of oxygen and sleep patterns interference was associated with environmental factors (too crowded). Implementation: The implementation of the nurse was by teaching a deep breath and cough effectively, motivating the patient to rest in between his activities and also motivating the patient to get enough sleep. Based on the implementation conducted, the result were 10 cc of sputum production, patient walked with a 10 meters distance by 3 sets with 1 set break and the patient could sleep soundly. Conclusion: Patients with COPD usually experienced shortness of breath and fatigue, therefore nursing care team should cooperate with patients and families to monitor oxygen therapy. Therapeutic communication could encourage more cooperative clients and could avoid things that cause shortness of breath recurred. Keywords: Chronic Obstructive Pulmonary Disease (COPD), shortness of breath, unhealthy lifestyle (smoking)